Pengaruh antara Kepemimpinan Primal, Budaya Organisasi dan Quality of Work Life dengan Perilaku Kewargaan Organisasi - Evi Dwi Iriani (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
The purpose of this study was to evaluate the influence of primal leadership and qualty of work life of organizational culture, leadership influence primal and qualty of work life towards citizenship behavior, and the impact of organizational culture on Organizational Citizenship Behaviour Unit DG Employment Renewable Energy and Energy Conservation. This study uses a quantitative approach to the design of an explanatory or causal. This research method using structural equation modeling (SEM) using 8.70 lisrel program, after testing the validity and reliability of research instruments by SPSS 20. Next, analysis of the data in this study using a test confirmatory factor analysis (CFA) and the weight Regression testing using structural equation modeling (SEM). The results of this study indicate that the CFA test on variables primal leadership, organizational culture, quality of work life and organizational citizenship behavior entirely generate significant value thus declared valid and relibel. Relationships leadership primal and qualty of work life against the culture of an organization is shown to have a significant relationship, then the relationship between the leadership of primal on the behavior of organizational citizenship is proven not have the significant relationship, while relations qualty of work life of the behavior of organizational citizenship proved to discount significant relationship, and the relationship of organizational culture on organizational citizenship behavior shown to have no significant relationship.